El nomen sacrum iħs como símbolo de la crucifixión en el Sermón de la Circuncisión del Señor de san Vicente Ferrer. - MANDINGORRA LLAVATA, MARÍA LUZ (Scripta, 2021)
The nomen sacrum iħs was present in many paintings as well as other artifacts during the Middle Ages, therefore, it was very well known by the public. The aim of this paper is to show the way Saint Vincent Ferrer uses this abbreviation as a symbol of the Crucifixion of Jesus Christ in order to increase the devotion to the Name of Jesus and prevent people from consulting diviners and sorcerers to solve daily life problems. To this end, we analyse the Sermon of the Circumcision of the Lord preached by the Dominican master and establish the relationship between the elements that compose the text and some contemporary images of the Crucifixion.